Cumulative effect of IFIH1 variants and increased gene expression associated with type 1 diabetes. Issue 2 (February 2015) - Zurawek, Magdalena; Fichna, Marta; Fichna, Piotr; Skowronska, Bogda; Dzikiewicz-Krawczyk, Agnieszka; Januszkiewicz, Danuta; Nowak, Jerzy
Highlights: The aim of this study was to analyze the associations of four SNPs in the IFIH1 locus with type 1 diabetes within Polish cohort and examine the expression level of IFIH1 gene in T1D patients. We indicated the association of all study variants with T1D. We also observed a cumulative effect of IFIH1 variants. T1D individuals with ≥6 risk alleles has increased risk of T1D with effect size 3.13. The results of association study stay in line with increased IFIH1 expression levels observed in T1D group. Current study is a first report of IFIH1 variants association and gene expression in Polish cohort of type 1 diabetes patients. We also indicated the cumulative effect of IFIH1 variants associated with T1D, that was not previously described. Abstract: Aims: IFIH1 (Interferon Induced with Helicase C domain 1) gene encodes a sensor of double-stranded RNA, which initiates antiviral activity. Recent studies have indicated the association of rare and common IFIH1 variants with type 1 diabetes mellitus (T1D). The aim of this study was to investigate whether polymorphisms in the IFIH1 locus are a risk factor for T1D in Caucasian patients from Poland. Methods: We genotyped 514 T1D patients and 713 healthy control individuals for rs3747517, rs1990760, rs2111485 and rs13422767 variants. Cumulative genetic risk score (CGRS) was calculated using unweighted and weighted approaches. We also examined the expression of IFIH1 gene in a cohort of 90 T1D patients. Results: All studied polymorphisms showed significant association with type 1 diabetes. The risk alleles G of rs3747517, rs2111485, rs13422767 and A of rs1990760 were observed more frequently in T1D group with P values and allelic odds ratio OR (95%CI) <0.0001, 1.742 (1.428–2.126); 0.001, 1.336 (1.125–1.588); <0.0001, 1.799 (1.416–2.285); 0.0005, 1.359 (1.144–1.616), respectively. The risk for type 1 diabetes increased with the growing number of the risk alleles. OR (95%CI) for carriers of ≥6 risk alleles reached 2.387 (1.552–3.670) for unweighted CGRS and 3.132 (1.928–5.089) for weighted CGRS. Furthermore, IFIH1 gene expression levels in unstimulated peripheral blood mononuclear cells of T1D patients were significantly higher compared to healthy individuals (mean ± SEM mRNA copy number 163.8 ± 15.7 vs . 117.8 ± 7.2; P  = 0.046). Conclusions: This study confirms the association of the IFIH1 locus with susceptibility to T1D in the Polish population. The cumulative effect of rs3747517, rs1990760, rs2111485 and rs13422767 variants on type 1 diabetes risk was observed.